Datos sobre la vegetación silicícola de Andalucia I. (Acta botánica malacitana, 1990)
: The phytocenologic study about climatophilous vegetation series, which inhibat on siliceous soils in Málaga, Cádiz, Sevilla and Granada (Spain), has produced the identification of six vegetation series. It is described the following new syntaxa: Smilaco mauritanicae-Quercetum rotundifOliae quercetosum suberis,Teucrio baetici-Querceturn suberis quercetosum rotundifoliae and Cytiso baetici-Arbutetum unedonis.